Desenhando a pele, tecendo práticas: a construção de saberes no trabalho do tatuador - Becker, Rubia Goi (2020)
Starting from the objective of understanding how and what knowledge is constituted in the practice of tattooing in daily work, we seek to explore the theme of organizational learning from the perspective of Practice Based Studies (PBS). In this sense, the practice of tattooing opens the way for the investigation of knowledge at work, which is recognized as the knowledge produced in the midst of everyday life in which the practice is carried out through the interaction between different knowledge, artifacts and practices. Based on AO theories with a sociological orientation, in the light of knowing-in-practice (GHERARDI, 2006b, 2012a) and aesthetic theory (STRATI, 1999a, 2007b), a relational orientation is assumed, understanding that the subjective aspects and the Sensitive knowledge can be linked to people's occupation - in this case, the practice of tattooing. For the operationalization of this study, ethnographic techniques were adopted, through participant observation and narrative interviews. Finally, data analysis will be performed using the technique of thematic analysis of narratives. It became evident that practices, knowledge, artifacts and sensitive knowledge are co-produced during work routines, either through communicating sensitive experiences by practitioners, or through observation and living in different situations in which the practice is performed. When mapping the practice of tattooing, five practices were predominant in the constitution of knowledge, namely: i) drawing; ii) assembly the workstation; iii) decal; iv) tattoo; and v) disassembly and disposal of the material. When identifying how these practices are ordered and connected in a texture of practices, knowing-in-practice has in essence the construction of a taste while the practice is performed, constituting from six knowledge: (i) creation and / or reproduction of the drawing; (ii) the actions and sayings related to each practice; (iii) manipulation of artifacts; (iv) the technique; (v) the movement of bodies; (vi) the activation of human senses. In addition to the diversity of knowledge linked to a series of heterogeneous practices, the results of the research signaled the production of the aesthetic judgment developed through socio-material interactions and sensitive knowledge. In this way, the knowledge imbricated to the practice of tattooing cannot be transferred from one individual to the other, since it is not possible to teach the sensitivity of the actions and sayings involved in the act of those who practice the activity, starting from an individual and unique construction of each practitioner from his sensitive knowledge and worldly perceptions.